Science and practice of strength training - Zatsiorsky, Vladimir M. (Vladimir Mikhailovich) 1932-; Kraemer, William J. 1953-; Fry, Andrew C. 1956-
"Science and Practice of Strength Training addresses the complexity of strength training programs while providing advice in customizing programs for athletes and other populations. It covers velocity training, intensity, timing, exercises, injury prevention, overtraining, and athlete monitoring"